Active energy ray-curable composition and laminate
The active energy ray-curable composition with cesium-containing composite tungsten oxide and (meth)acryloyl compounds addresses the issues of insufficient infrared blocking and curling in plastic substrates, achieving high transparency, light blocking, and scratch resistance in a thin film laminate.
Patent Information
- Application Number
- JP2023110637
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2043-07-05
AI Technical Summary
Existing plastic substrates coated with active energy ray-curable compositions for improving surface properties suffer from insufficient light blocking in the infrared region, curling issues, and reduced abrasion resistance when increasing composite tungsten oxide particle content, while maintaining transparency and scratch resistance.
An active energy ray-curable composition containing 30 to 70% composite tungsten oxide particles, specifically cesium-containing composite tungsten oxide, along with compounds having three or more (meth)acryloyl groups, is used to form a resin layer with a haze of 1.0% or less and total light transmittance of 65% or more in the visible light range and 20% or less in the near-infrared range, while providing excellent scratch resistance and minimizing curling.
The composition achieves high light transmittance in the visible light range, effective light blocking in the near-infrared range, and superior scratch resistance with reduced curling, forming a thin film laminate with enhanced properties.
Smart Images

Figure 2025008453000001 
Figure 2025008453000002 
Figure 2025008453000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable composition, and a laminate including a resin layer which is a cured product of the active energy ray-curable composition, and a light-transmitting substrate. [Background technology]
[0002] Substrates made of plastics such as polyethylene terephthalate (PET) resin are excellent in transparency and impact resistance, and are lightweight and easy to process, so they are used in various applications in place of glass substrates.
[0003] However, plastic substrates may be inferior to glass substrates in terms of surface properties such as hardness and scratch resistance, etc. For this reason, it is common to coat an active energy ray-curable composition on the surface of a plastic substrate to form a cured layer, thereby improving the surface properties of the plastic substrate.
[0004] Meanwhile, as one concrete measure against recent climate change, attention is being paid to blocking light in the near-infrared range (wavelengths 800 to 2,500 nm), also known as "heat rays" because they are contained in sunlight and have a strong heating effect, thereby saving energy by preventing the temperature rise in living environments.
[0005] In response to this, in recent years, various means have been developed for maintaining brightness by blocking heat rays while allowing sufficient intake of visible light (wavelengths of 380 to 780 nm). For example, a method has been disclosed in which a heat ray-shielding film having a resin layer formed by curing an active energy ray-curable composition containing antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), or composite tungsten oxide particles, which are inorganic infrared absorbents with excellent light-blocking properties in the near-infrared range, is attached to a window (Patent Document 1).
[0006] However, in Patent Document 1, the content of the composite tungsten oxide particles is low, so the light blocking property in the infrared region is insufficient. In addition, in order to increase the light blocking property in the infrared region (to increase the absolute amount of the composite tungsten oxide particles), it is necessary to coat the resin layer with a thickness of 4 μm, which causes a problem of curling due to the curing shrinkage of the active energy ray curable composition. In addition, in the invention of Patent Document 1, simply increasing the content of the composite tungsten oxide particles results in a decrease in abrasion resistance and an increase in haze, and there was no invention that could satisfy visible light transmittance, near-infrared cut property, abrasion resistance, and curling property. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2008-200983 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide an active energy ray-curable composition for forming a resin layer that has excellent light transmittance in the visible light range (wavelength 380 nm to 780 nm), light blocking properties in the near-infrared range (wavelength 800 nm to 2,500 nm), and surface scratch resistance, and is also resistant to curling. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems, and as a result have arrived at the following invention. The present invention provides the following active energy ray-curable composition, resin layer, and laminate.
[0010] [1]: An active energy ray-curable composition comprising a compound (A) having three or more (meth)acryloyl groups, composite tungsten oxide particles (B) and a photopolymerization initiator (C), and which simultaneously satisfies the following (1) and (2): (1) The content of the composite tungsten oxide particles (B) in 100% by mass of the non-volatile components of the active energy ray-curable composition is 30 to 70% by mass. (2) In a test piece having a 1 μm-thick resin layer which is a cured product of an active energy ray-curable composition on a 50 μm-thick polyethylene terephthalate film, the haze is 1.0% or less, the total light transmittance is 65% or more, the light transmittance at a wavelength of 500 nm is 75% or more, and the light transmittance at wavelengths of 1,000 nm and 2,000 nm is 20% or less.
[0011] [2]: The active energy ray-curable composition, wherein the composite tungsten oxide particles (B) are cesium-containing composite tungsten oxide particles.
[0012] [3]: The active energy ray-curable composition, wherein the compound (A) includes a compound having 6 or more (meth)acryloyl groups.
[0013] [4]: The active energy ray-curable composition, characterized in that it contains 30 to 69 mass% of a compound (a1) having 6 or more (meth)acryloyl groups and having a cyclic structure, based on 100 mass% of the non-volatile components of the active energy ray-curable composition.
[0014] [5]: A laminate having a light-transmitting substrate (α) and a resin layer (β) which is a cured product of the active energy ray-curable composition. Effect of the Invention
[0015] The present invention makes it possible to provide an active energy ray-curable composition for forming a resin layer which has light transmittance in the visible light range, high light blocking properties in the near-infrared range even when it is a thin film, excellent surface scratch resistance, and is less likely to curl. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described in detail below. Needless to say, other embodiments are also included in the scope of the present invention as long as they are consistent with the gist of the present invention. In this specification, a numerical range specified using "~" includes the numerical values written before and after "~" as the lower and upper limit ranges. In addition, various components appearing in this specification may be used independently alone or in combination of two or more types, unless otherwise noted.
[0017] First, the terms used in this specification will be explained. In this specification, unless otherwise specified, the terms "(meth)acrylic", "(meth)acryloyl", and "(meth)acrylate" mean "acrylic or methacrylic", "acryloyl or methacryloyl", and "acrylate or methacrylate", respectively. Furthermore, an "active energy ray-curable composition" may be referred to as a "composition," an "active energy ray-curable compound (A) having three or more (meth)acryloyl groups" may be referred to as a "compound (A)," a "compound (a1) having six or more (meth)acryloyl groups and having a cyclic structure" may be referred to as a "compound (a1)," a "compound (a2) having six or more (meth)acryloyl groups excluding (a1)" may be referred to as a "compound (a2)," and a "compound (a3) having 3 to 5 (meth)acryloyl groups" may be referred to as a "compound (a3)."
[0018] <<Active energy ray-curable composition>> The active energy ray-curable composition of the present invention contains an active energy ray-curable compound (A) having three or more (meth)acryloyl groups, composite tungsten oxide particles (B), and a photopolymerization initiator (C).
[0019] The active energy ray-curable composition of the present invention, in a test piece having a 1 μm-thick resin layer which is a cured product of the active energy ray-curable composition on a 50 μm-thick polyethylene terephthalate film, has a haze of 1.0% or less, a total light transmittance of 65% or more, a light transmittance at a wavelength of 500 nm of 75% or more, and a light transmittance at wavelengths of 1,000 nm and 2,000 nm of 20% or less. From the viewpoint of blocking heat rays, the light transmittance at wavelengths of 1,000 nm and 2,000 nm is preferably 15% or less, and more preferably 10% or less at wavelengths of 1,000 nm and 2,000 nm.
[0020] Such an active energy ray curable composition makes it possible to form a resin layer that has excellent light transmittance in the visible light region, light blocking properties in the near infrared region, and excellent scratch resistance on the surface of the resin layer that is the cured layer of the active energy ray curable composition, and that is less likely to curl when formed into a laminate. The method for preparing the test piece and the method for measuring the haze, total light transmittance, and light transmittance at each wavelength are described in detail in the Examples section.
[0021] <Compound (A)> The compound (A) may be any compound having three or more (meth)acryloyl groups, and may be a low molecular weight compound, a high molecular weight compound, or the like, regardless of molecular weight.
[0022] From the viewpoint of increasing the surface hardness of the resin layer (β) which is a cured product of the active energy ray-curable composition, the compound (A) is preferably used in an amount of 20 to 69 mass%, more preferably 30 to 69 mass%, and further preferably 40 to 69 mass%, based on 100 mass% of the non-volatile components of the active energy ray-curable composition.
[0023] Compound (A) is roughly classified into compounds (a1) having six or more (meth)acryloyl groups and having a cyclic structure, compounds (a2) having six or more (meth)acryloyl groups and not having a cyclic structure, and compounds (a3) having 3 to 5 (meth)acryloyl groups. From the viewpoint of excellent scratch resistance of the resin layer (β) surface, the compound (A) preferably contains a compound having 6 or more (meth)acryloyl groups. That is, it is preferable to contain at least one of (a1) and (a2). Among them, from the viewpoint of forming a resin layer that is less likely to curl when made into a laminate, it is more preferable to contain (a1). Furthermore, (a3) can be blended as necessary within a range that does not impair the effects of the present invention.
[0024] (Compound (a1)) The compound (a1) has six or more (meth)acryloyl groups and has a cyclic structure. Examples of the cyclic structure include an aromatic ring structure, an alicyclic structure consisting of a saturated or unsaturated carbon ring having no aromaticity, and a nurate ring structure which is a trimer of an isocyanate compound having a nitrogen atom and is a six-membered ring structure, and the alicyclic structure and nurate ring structure are preferred in order to prevent discoloration of the aromatic ring due to ultraviolet light, heat, etc. By having six or more (meth)acryloyl groups, the crosslink density is increased, the scratch resistance of the surface of the resin layer (β) is excellent, and curling of the resin layer (β) can be suppressed.
[0025] From the viewpoint of curling prevention, the compound (a1) is preferably used in an amount of 30 to 69 mass%, more preferably 40 to 69 mass%, and even more preferably 50 to 69 mass%, based on 100 mass% of the nonvolatile components of the active energy ray-curable composition.
[0026] Specific examples of the compound (a1) include a reaction product of an alicyclic diisocyanate or an aromatic diisocyanate with a poly(meth)acrylate compound having a hydroxyl group, a reaction product of an isocyanurate (trimer) of a diisocyanate with a poly(meth)acrylate compound having a hydroxyl group, and a reaction product of an alicyclic polyisocyanate or an aromatic polyisocyanate or an isocyanurate (trimer) of a polyisocyanate with a polyol and a poly- or mono(meth)acrylate compound having a hydroxyl group. Among these, from the viewpoint of excellent scratch resistance of the surface of the resin layer (β), a reaction product of an alicyclic diisocyanate with a poly(meth)acrylate compound having one hydroxyl group and three or more (meth)acryloyl groups, or a reaction product of an isocyanurate (trimer) compound of a diisocyanate (excluding alicyclic diisocyanates) with a poly(meth)acrylate compound having one hydroxyl group and two or more (meth)acryloyl groups is preferred.
[0027] Examples of alicyclic diisocyanates include cyclohexane-1,4-diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, dimeryl diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, and dimer diisocyanate in which the carboxy group of a dimer acid is converted into an isocyanate group, but are not limited to these.
[0028] Examples of aromatic diisocyanates include, but are not limited to, 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, m-tetramethylxylylene diisocyanate, 4,4-diphenylmethane diisocyanate, xylylene diisocyanate, and 2,6-diisocyanate-benzyl chloride.
[0029] Diisocyanates (excluding alicyclic diisocyanates and aromatic diisocyanates) include, but are not limited to, aliphatic diisocyanurates such as hexamethylene diisocyanate.
[0030] Examples of mono(meth)acrylates having a hydroxyl group include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of poly(meth)acrylates having a hydroxyl group include trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and cyclohexane. Examples of the hydroxyl group-containing (meth)acrylic acid ester include, but are not limited to, cyclohexanedimethanol mono(meth)acrylic acid ester, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, ethyl-α-(hydroxymethyl) (meth)acrylate, monofunctional glycerol (meth)acrylate, or (meth)acrylic acid esters having a hydroxyl group at the end obtained by ring-opening addition of these (meth)acrylates with ε-caprolactone lactone, and alkylene oxide-added (meth)acrylic acid esters obtained by repeatedly adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to the above-mentioned hydroxyl group-containing (meth)acrylates.
[0031] Examples of the polyol include ethylene glycol, propylene glycol, dipropylene glycol, diethylene glycol, triethylene glycol, butylene glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 3,3'-dimethylolheptane, 2-butyl-2-ethyl-1,3-propanediol, polyoxyethylene glycol (addition mole number 10 or less), polyoxypropylene glycol (addition mole number 10 or less), and the like. Examples of the diols include, but are not limited to, aliphatic or alicyclic diols such as propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, neopentyl glycol, octanediol, butylethylpentanediol, 2-ethyl-1,3-hexanediol, cyclohexanediol, cyclohexanedimethanol, tricyclodecane dimethanol, cyclopentadiene dimethanol, and dimer diol.
[0032] (Compound (a2)) Compound (a2) is a compound having 6 or more (meth)acryloyl groups and not having a cyclic structure. (a2) may be an oligomer or a polymer. In this specification, oligomer and polymer are polymers in which a finite number of monomers are bonded, oligomer refers to a compound having a weight average molecular weight of 10,000 or less, and polymer refers to a compound having a weight average molecular weight of more than 10,000. Oligomers and polymers may be homopolymers or copolymers. In this specification, the weight average molecular weight is a value measured by gel permeation chromatography (GPC) using polystyrene with a known weight average molecular weight as a standard substance.
[0033] From the viewpoint of scratch resistance, the compound (a2) is preferably used in an amount of 30 to 69 mass%, more preferably 40 to 69 mass%, and even more preferably 50 to 69 mass%, based on 100 mass% of the nonvolatile components of the active energy ray-curable composition.
[0034] Specific examples of the compound (a2) include, for example, Hexafunctional (meth)acrylate compounds such as dipentaerythritol hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate, Examples include polyurethane-based (meth)acrylate compounds having six or more (meth)acryloyl groups, polyester-based (meth)acrylate compounds having six or more (meth)acryloyl groups, and epoxy-based (meth)acrylate compounds having six or more (meth)acryloyl groups, which do not contain a cyclic structure.
[0035] Examples of polyurethane-based (meth)acrylate compounds include those obtained by reacting a diisocyanate with a (meth)acrylate having a hydroxyl group, and those obtained by reacting an isocyanate group-containing urethane prepolymer obtained by reacting a polyol with a polyisocyanate under conditions of excess isocyanate groups with a (meth)acrylate having a hydroxyl group, etc. Alternatively, they can also be obtained by reacting a hydroxyl group-containing urethane prepolymer obtained by reacting a polyol with a polyisocyanate under conditions of excess hydroxyl groups with a (meth)acrylate having an isocyanate group.
[0036] As the polyisocyanate, known ones can be used, and examples thereof include aliphatic diisocyanates. Examples of the aliphatic diisocyanate include butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate.
[0037] Examples of the hydroxyl group-containing (meth)acrylate include the same as those mentioned above, and among them, those containing at least one selected from trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate are preferred.
[0038] The polyester-based (meth)acrylate compound can be obtained, for example, by reacting a polyester polycarboxylic acid obtained by polycondensing a polybasic acid and a polyalcohol with a hydroxyl group-containing (meth)acrylate or the like. The polybasic acid may be an aliphatic acid, and may be used without any particular limitation. For example, the aliphatic polybasic acid may be oxalic acid, malonic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, suberic acid, maleic acid, fumaric acid, dodecanedioic acid, pimelic acid, citraconic acid, glutaric acid, itaconic acid, succinic anhydride, maleic anhydride, etc., and these aliphatic dicarboxylic acids and their anhydrides may be used. Also, derivatives of the acid anhydrides may be used.
[0039] Examples of the polyol include the same as those mentioned above.
[0040] Furthermore, polyols containing three or more hydroxyl groups, such as glycerin, trimethylolpropane, pentaerythritol, and dipentaerythritol, may also be used in part.
[0041] Examples of the hydroxyl group-containing (meth)acrylate include the same as those mentioned above, and among them, those containing at least one selected from trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate are preferred.
[0042] Examples of epoxy-based (meth)acrylate compounds include those in which the glycidyl group of an epoxy resin is esterified with (meth)acrylic acid to form a (meth)acrylate group as a functional group.
[0043] (Compound (a3)) The compound (a3) is a compound having 3 to 5 (meth)acryloyl groups, and examples thereof include, but are not limited to, the following compounds.
[0044] From the viewpoint of scratch resistance, the content of compound (a3) is preferably 69 mass% or less, more preferably 50 mass% or less, and even more preferably 30 mass% or less, based on 100 mass% of the non-volatile components of the active energy ray-curable composition.
[0045] Examples of the pentafunctional (meth)acrylate include dipentaerythritol penta(meth)acrylate and alkyl-modified dipentaerythritol penta(meth)acrylate.
[0046] Examples of tetrafunctional (meth)acrylates include dimethylolpropane tetra(meth)acrylate, ethylene oxide modified dimethylolpropane tetra(meth)acrylate, propylene oxide modified dimethylolpropane tetra(meth)acrylate, tetramethylene oxide modified dimethylolpropane tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate.
[0047] Examples of the trifunctional tri(meth)acrylate include trimethylolpropane tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, tetramethylene oxide-modified trimethylolpropane tri(meth)acrylate, tris(acryloxyethyl)isocyanurate, caprolactone-modified tris(acryloxyethyl)isocyanurate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, alkyl-modified dipentaerythritol tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, ethylene oxide-modified glycerol triacrylate, propylene oxide-modified glycerol triacrylate, ε-caprolactone-modified trimethylolpropane triacrylate, and pentaerythritol triacrylate.
[0048] <Composite tungsten oxide particles (B)> The composite tungsten oxide particles include composite tungsten oxide particles represented by general formula (1). M m WO n …(1) (In the formula, M represents one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, and I; W represents tungsten; O represents oxygen; and m and n are numbers that satisfy 0.001≦m≦1.0 and 2.2≦n≦3.0.)
[0049] The composite tungsten oxide represented by the general formula (1) has excellent durability when it has a hexagonal, tetragonal, or cubic crystal structure, so it is preferable that it contains one or more crystal structures selected from the hexagonal, tetragonal, and cubic crystal structures. Among these, the hexagonal crystal structure is particularly preferable because it has the smallest absorption in the visible light range. For example, the composite tungsten oxide having a hexagonal crystal structure may include a composite tungsten oxide containing one or more elements selected from the elements Cs, Rb, K, Tl, In, Ba, Li, Ca, Sr, Fe, and Sn as the preferred M element. The amount m of the M element added in the composite tungsten oxide is preferably 0.001 or more and 1.0 or less, and more preferably about 0.33. This is because the value of m theoretically calculated from the hexagonal crystal structure is 0.33, and an amount added around this value provides favorable optical properties as an infrared absorbing agent. On the other hand, the amount n of oxygen present is preferably 2.2 or more and 3.0 or less. A typical example is Cs 0.33 WO3, Rb 0.33 WO3, K 0.33 WO3, Ba 0.33 WO3, etc., and as long as m and n fall within the above ranges, useful near-infrared blocking properties can be obtained.
[0050] In the present invention, a cesium-containing composite tungsten oxide is preferable from the viewpoint of light transmittance in the visible light region and light blocking properties in the near infrared region. Cs 0.2~0.4 WO 2.5~3.0 …(2) Examples of the compound include compounds represented by the following formula:
[0051] The primary particle diameter of the composite tungsten oxide particles is preferably 10 to 500 nm, more preferably 10 to 200 nm, and even more preferably 10 to 100 nm, from the viewpoints of dispersibility, optical properties, etc. The average particle diameter (median diameter) is preferably 10 to 1000 nm, more preferably 10 to 500 nm, and even more preferably 10 to 100 nm.
[0052] The average particle size can be measured by a particle size distribution measuring device, particularly a particle size distribution measuring device using a dynamic light scattering method (such as "NANOTRAC WAVE II EX150" manufactured by Microtrack-Bell, Inc.). In the present invention, a methyl ethyl ketone / methoxybutanol = 1 / 1 mixed solvent was used as the solvent, and the average value of three 60-second measurements was used at a concentration in which the loading index was in the range of 1.0 ± 0.2.
[0053] In the present invention, the composite tungsten oxide particles may be used alone or in combination of two or more kinds.
[0054] The content of the composite tungsten oxide particles is 30 to 70 mass %, preferably 30 to 60 mass %, based on 100 mass % of the non-volatile components of the active energy ray curable composition. This content allows for an excellent balance of light transmittance in the visible light region, light blocking properties in the near infrared region, dispersibility, and surface hardness of the resin layer (β) which is the cured product of the active energy ray curable composition.
[0055] <Photopolymerization initiator (C)> As the photopolymerization initiator (C), for example, a monocarbonyl-based photopolymerization initiator, a dicarbonyl-based photopolymerization initiator, an acetophenone-based photopolymerization initiator, a benzoin ether-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, an aminocarbonyl-based photopolymerization initiator, etc. The photopolymerization initiator (C) may be used in combination with a sensitizer.
[0056] Specific examples of the photopolymerization initiator (C) include monocarbonyl photopolymerization initiators such as benzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, methyl-o-benzoylbenzoate, 4-phenylbenzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 2- / 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, and 1-chloro-4-propoxythioxanthone; dicarbonyl photoinitiators such as 2-ethylanthraquinone, 9,10-phenanthrenequinone, and methyl-α-oxobenzeneacetate; acetophenone-based photoinitiators such as 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxy-cyclohexyl phenyl ketone, diethoxyacetophenone, dibutoxyacetophenone, 2,2-dimethoxy-1,2-diphenylethan-1-one, 2,2-diethoxy-1,2-diphenylethan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, and 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime; benzoin ether-based photopolymerization initiators such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzoin normal butyl ether; Acylphosphine oxide photoinitiators such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 4-n-propylphenyl-di(2,6-dichlorobenzoyl)phosphine oxide; and aminocarbonyl photopolymerization initiators such as ethyl-4-(dimethylamino)benzoate, 2-n-butoxyethyl-4-(dimethylamino)benzoate, isoamyl-4-(dimethylamino)benzoate, 2-(dimethylamino)ethyl benzoate, 4,4'-bis-4-dimethylaminobenzophenone, 4,4'-bis-4-diethylaminobenzophenone, and 2,5'-bis(4-diethylaminobenzal)cyclopentanone; etc.
[0057] Commercially available photopolymerization initiators (C) include Omnirad184, 651, 500, 907, 127, 369, 784, 2959, and Esacure One manufactured by IGM-Resins BV, and Lucirin TPO manufactured by BASF Ltd. In particular, Omnirad184 and Esacure One are preferred from the viewpoint of yellowing resistance after curing with active energy rays.
[0058] The content of the photopolymerization initiator (C) is not limited as long as it is contained in an amount that allows the resin layer to be cured by ultraviolet light to have predetermined physical properties. From the viewpoints of the curing speed and the hardness and scratch resistance of the cured resin layer, however, the content is preferably 1 to 15 mass %, and more preferably 3 to 10 mass %, relative to 100 mass % of the nonvolatile components of the active energy ray-curable composition.
[0059] (Organic solvent) The active energy ray-curable composition of the present invention may contain an organic solvent. Examples of the organic solvent that can be used include known organic solvents such as aromatic organic solvents, such as toluene and xylene; ketone-based organic solvents, such as methyl ethyl ketone and methyl isobutyl ketone; ester-based organic solvents, such as ethyl acetate, n-propyl acetate, isopropyl acetate, and isobutyl acetate; alcohol-based organic solvents, such as methanol, ethanol, n-propanol, isopropanol, and n-butanol; and glycoether-based organic solvents, such as propylene glycol monomethyl ether.
[0060] When an organic solvent is contained, the content of the organic solvent is preferably in a range such that the non-volatile concentration of the active energy curable composition of the present invention is 1 to 70 mass %, from the viewpoints of coatability and film-formability.
[0061] (Other ingredients) The active energy ray-curable composition of the present invention may contain, as necessary, an additive, an active energy ray-curable compound having one to two (meth)acryloyl groups, an active energy ray-curable compound having a radical polymerizable group other than a (meth)acryloyl group, such as a vinyl group or an allyl group, a resin component not having a (meth)acryloyl group, and the like. Examples of the additives include thermosetting resins, polymerization inhibitors, leveling agents, slip agents, defoamers, surfactants, antibacterial agents, antiblocking agents, plasticizers, ultraviolet absorbers, infrared absorbers, antioxidants, silane coupling agents, conductive agents, inorganic particles, pigments, and dyes.
[0062] <Laminate> The laminate of the present invention has a light-transmitting substrate (α) and a resin layer (β). A laminate can be obtained by applying the active energy ray curable composition of the present invention onto a light-transmitting substrate (α) and forming a resin layer (β) cured by active energy rays. The conditions for applying the active energy ray curable composition onto the surface of the light-transmitting substrate (α) (one or both sides if the substrate is, for example, a film-like substrate) are not particularly limited, and examples of the application method include a spray, a roll coater, a reverse roll coater, a gravure coater, a knife coater, a bar coater, and a dot coater. The thickness of the hard coat layer is not particularly limited, but is preferably 1 to 10 μm, more preferably 1 to 5 μm, and even more preferably 1 to 3 μm.
[0063] <Light transparent base material (α)> The light-transmitting substrate (α) functions as a support layer for the resin layer (β). Here, the light transmittance means that the transmittance of light of a necessary wavelength is 80% or more when measured through the thickness of the light-transmitting substrate (α) in the laminate. It is more preferably 85% or more, and even more preferably 90% or more. When the laminate is used for an application requiring transparency, the light of a necessary wavelength corresponds to light in the visible light region (wavelength 380 to 780 nm). The light-transmitting substrate (also called a support) is not particularly limited, and examples thereof include glass, synthetic resin moldings, and films.
[0064] Examples of synthetic resin moldings include moldings of synthetic resins such as polymethyl methacrylate resin, copolymer resins mainly composed of methyl methacrylate, polystyrene resin, styrene-methyl methacrylate copolymer resin, styrene-acrylonitrile copolymer resin, polycarbonate resin, cellulose acetate butyrate resin, polyallyl diglycol carbonate resin, polyvinyl chloride resin, and polyester resin.
[0065] Examples of films include polyester films, polyethylene films, polypropylene films, cellophane films, diacetyl cellulose films, triacetyl cellulose (TAC) films, acetyl cellulose butyrate films, polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene vinyl alcohol films, polyolefin films, polystyrene films, polycarbonate films, polymethylpentel films, polysulfone films, polyether ether ketone films, polyether sulfone films, polyether imide films, polyimide films, fluororesin films, nylon films, and acrylic films.
[0066] <Resin layer (β)> The resin layer (β) can be obtained by curing the active energy ray-curable composition of the present invention with active energy rays. Examples of active energy rays include ultraviolet rays and electron beams. Examples of sources of ultraviolet rays include high-pressure mercury lamps and metal halide lamps, and the irradiation energy is usually 100 to 2,000 mJ / cm. 2 Examples of the electron beam supply method include scanning electron beam irradiation and curtain electron beam irradiation, and the irradiation energy is usually about 10 to 200 kGy. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples and comparative examples, but the following examples are not intended to limit the technical scope of the present invention. In the examples, "parts" means "parts by mass" and "%" means "% by mass". The blend amounts in the table are in parts by mass, and amounts other than the solvent are calculated as non-volatile contents. Note that blanks in the table indicate that no blend was made.
[0068] The raw materials used in the synthesis examples, working examples, and comparative examples are shown in Table 1.
[0069] [Table 1]
[0070] [Synthesis example] As the compound (a1) having six or more (meth)acryloyl groups and a cyclic structure, urethane acrylate compounds (a1-1) to (a1-7) are used. As the compound (a2) having six or more (meth)acryloyl groups and not having a cyclic structure, urethane acrylate compounds (a2-2) and (a2-3) are used. A urethane acrylate compound (a3-1) was synthesized as a compound (a3) having 3 to 5 (meth)acryloyl groups. (The urethane acrylate compound will be abbreviated as urethane acrylate or compound.)
[0071] <Synthesis of urethane acrylate (a1-1)> (Synthesis Example 1) Urethane acrylate mixed liquid (A1): 596.5 parts by mass of PE-3A (manufactured by Thermo FS, pentaerythritol triacrylate (a3-2)) and 0.1 parts by mass of Neostan U-810 (manufactured by Nitto Kasei, tin catalyst) were placed in a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, and the liquid temperature was raised to 50°C. After that, 223.2 parts by mass of VESTANAT IPDI (manufactured by EVONIK, isophorone diisocyanate) was added dropwise from the dropping funnel over a period of 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the isocyanate group peak had disappeared by Fourier transform infrared spectroscopy (FT-IR), the temperature was lowered to room temperature to obtain a urethane acrylate mixture (A1) containing 99.9 mass% of urethane acrylate (a1-1) having 6 acryloyl groups and a weight average molecular weight of 819 and 0.1 mass% of a polyisocyanate condensate. The amount of the polyisocyanate condensate was calculated from formula (3) (wherein J is the polyisocyanate condensate content per polyisocyanate molecule, K is the molecular weight of the polyisocyanate, L is the NCO content (mass%) in the polyisocyanate raw material composition (non-volatile content), M is the molecular weight of NCO, and N is the number of NCO units per polyisocyanate molecule). J = (M × N / L) - K … (3)
[0072] (Synthesis Example 2) to (Synthesis Example 17): In the same manner as in Synthesis Example (1), urethane acrylate mixed solutions (A2) to (A17) containing urethane acrylates (a1-2) to (a1-7), (a2-1) to (a2-3), (a3-1), and (a3-5) were obtained with the formulations shown in Table 2.
[0073] [Table 2]
[0074] <Production of cesium composite tungsten oxide (b1) particle dispersion (B1)> Cesium composite tungsten oxide particles (b1) (Keeling & Walker, IRASORB CTO) 40.0 parts, dispersant (manufactured by DISPERBYK142) 4.0 parts, and methyl ethyl ketone (D1) / methoxybutanol (D2) = 1 / 1 mixed solvent 56.0 parts were mixed, and pre-dispersion (zirconia beads (0.5 mm) were used as a medium, and dispersed with a paint shaker for 1 hour) was performed, followed by adding methyl ethyl ketone (D1) / methoxybutanol (D2) = 1 / 1 mixed solvent 60.0 parts, and then main dispersion (zirconia beads (0.1 mm) were used as a medium, and dispersed with a dispersing machine UAM-015 manufactured by Kotobuki Kogyo Co., Ltd.) to obtain a cesium composite tungsten oxide particle (b1) dispersion (B1) (cesium composite tungsten oxide particle (b1) concentration 25.0 mass%, dispersant concentration 2.5 mass%, average particle diameter 19 nm). <Production of antimony-doped tin oxide (ATO) (b2) particle dispersion (B2)> An antimony-doped tin oxide (ATO) (b2) particle dispersion (B2) (antimony-doped tin oxide (ATO) (b2) concentration 25.0 mass%, dispersant concentration 2.5 mass%, average particle diameter 85 nm) was obtained in the same manner as in the production of the cesium composite tungsten oxide (b1) particle dispersion (B1), except that the cesium composite tungsten oxide particles (b1) (IRASORB CTO, manufactured by Keeling & Walker) were changed to antimony-doped tin oxide (ATO) (b2) (conductive powder T-1, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.). <Production of tin-doped indium oxide (ITO) (b3) particle dispersion (B3)> A tin-doped indium oxide (ITO) (b3) particle dispersion (B3) (tin-doped indium oxide (ITO) (b3) concentration 25.0 mass%, dispersant concentration 2.5 mass%, average particle diameter 65 nm) was obtained in the same manner as in the production of the cesium composite tungsten oxide (b1) particle dispersion (B1), except that the cesium composite tungsten oxide particles (b1) (IRASORB CTO, manufactured by Keeling & Walker) were changed to tin-doped indium oxide (ITO) (b3) (IRASORB B-ITO, manufactured by Keeling & Walker).
[0075] Example 1: Preparation of active energy ray-curable composition Into a flask equipped with a stirrer, 63.0 parts by mass of the urethane acrylate mixed solution (A1), 120.0 parts of the cesium composite tungsten oxide (b1) dispersion solution (B1), 4.0 parts of the photopolymerization initiator IRGACURE184 (C1), and 213.0 parts of methyl ethyl ketone (D1) were added and mixed with stirring to obtain an active energy ray curable composition containing the following compounds. Urethane acrylate (a1-1): 62.9 parts Polyisocyanate condensate: 0.1 parts by weight Cesium composite tungsten oxide particles (b1): 30.0 parts Dispersant: 3.0 parts Photopolymerization initiator (C1): 4.0 parts Hard coat layer forming composition (non-volatile content): 100 parts Methyl ethyl ketone (D1): 256.5 parts Methoxybutanol (D2): 43.5 parts Active energy ray curable composition: 400 parts in total
[0076] (Examples 2 to 30 and Comparative Examples 1 to 6): Preparation of active energy ray-curable compositions In the same manner as in Example 1, active energy ray-curable compositions were prepared according to the formulations shown in Tables 3-1 to 3-4.
[0077] The materials used in the examples and comparative examples are described below.
[0078] <Compound (a1) Having Six or More (Meth)acryloyl Groups and a Cyclic Structure> a1-1: A urethane acrylate compound, a reaction product of IPDI and PE-3A, with a molecular weight of 819 and 6 acryloyl groups. a1-2: A urethane acrylate compound, a reaction product of IPDI nurate and PE-3A, with a molecular weight of 1562 and 9 acryloyl groups. a1-3: A urethane acrylate compound, a reaction product of IPDI and PE-5A, with a molecular weight of 1271 and 10 acryloyl groups. a1-4: A urethane acrylate compound, a reaction product of IPDI nurate and DPE-5A, with a molecular weight of 2240 and 15 acryloyl groups. a1-5: A urethane acrylate compound, a reaction product of hydrogenated MDI and PE-3A, with a molecular weight of 859 and 6 acryloyl groups. a1-6: A urethane acrylate compound, a reaction product of HDI nurate and PE-3A, with a molecular weight of 1399 and 9 acryloyl groups. a1-7: A urethane acrylate compound, a reaction product of MDI and PE-3A, with a molecular weight of 847 and 6 acryloyl groups. <Compound (a2) Having Six or More (Meth)acryloyl Groups and No Cyclic Structure> A2-1: Dipentaerythritol hexaacrylate, molecular weight 579, 6 acryloyl groups a2-2: A urethane acrylate compound, a reaction product of HDI and PE-3A, with a molecular weight of 765 and 6 acryloyl groups. a2-3: A urethane acrylate compound, a reaction product of HDI and DPE-5A, with a molecular weight of 1217 and 10 acryloyl groups.
[0079] <Compound (a3) Having 3 to 5 (Meth)acryloyl Groups> a3-1: A urethane acrylate compound, a reaction product of IPDI nurate and 4HBA, with a molecular weight of 1099 and 3 acryloyl groups. a3-2: Pentaerythritol triacrylate (PE-3A): molecular weight 298, 3 acryloyl groups a3-3: Pentaerythritol tetraacrylate (PE-4A): molecular weight 352, 4 acryloyl groups a3-4: Isocyanuric EO modified triacrylate: molecular weight 432, 3 acryloyl groups a3-5: Dipentaerythritol pentaacrylate (DPE-5): molecular weight 524, 5 acryloyl groups
[0080] <Other components: Compound (a4) having two (meth)acryloyl groups> Diacrylate compound (a4-1): Osaka Organic Chemical Industry Co., Ltd., Viscoat #230, HDDA (HD-2A): 1,6-Hexanediol diacrylate: molecular weight 226.3, number of acryloyl groups 2 Isocyanurate EO modified diacrylate (a4-2): molecular weight 369, 2 acryloyl groups
[0081] <Composite tungsten oxide particles (B)> Cesium composite tungsten oxide particles (b-1) (Keeling & Walker, IRASORB CTO)
[0082] <Other metal oxide particles> Antimony-doped tin oxide (ATO) (b'-1) (Mitsubishi Materials Electronics Co., Ltd., conductive powder T-1) Tin-doped indium oxide (ITO) (b'-2) (Keeling & Walker, IRASORB B-ITO)
[0083] Dispersant (BYK, DISPERBYK142)
[0084] <Photopolymerization initiator (C)> Irgacure 184(C1): BASF
[0085] <Solvent (D)> (D1) Methyl ethyl ketone (Maruzen Petrochemical Co., Ltd.) (D2) Methoxybutanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0086] [Table 3-1]
[0087] [Table 3-2]
[0088] [Table 3-3]
[0089] [Table 3-4]
[0090] [Example 1]: Preparation of resin layer (β) and laminate The active energy curable composition obtained above was applied to a 50 μm thick film using a bar coater so that the film thickness after drying would be 1 μm, and then the applied composition was exposed to 400 mJ / cm 2 with a high pressure mercury lamp. 2 The resin layer (β) was formed by irradiating the resin with ultraviolet light of 1000 nm to prepare a laminate.
[0091] [Examples 2 to 30 and Comparative Examples 1 to 6]: Preparation of resin layer (β) and laminate A laminate was produced in the same manner as in Example 1.
[0092] <Haze (HZ)> The haze (HZ) of the laminate produced above was measured in accordance with JIS K 7136 using a Haze Meter SH7000 manufactured by Nippon Denshoku Industries Co., Ltd. The measurement was performed from the resin layer (β) side. [Evaluation Criteria] ·0.8% or less: Good Over 0.8% and up to 1.0%: No practical problems Over 1.0%: Not practical
[0093] ≪Total light transmittance≫ The total light transmittance of the produced laminate was measured in accordance with JIS K 7375 using a "Haze Meter SH7000" manufactured by Nippon Denshoku Industries Co., Ltd. The measurement was performed from the resin layer (β) side. If it is 65% or more, there is no problem in practical use.
[0094] ≪Spectral transmittance≫ The light transmittance of the produced laminate at 500 nm, 1,000 nm, and 2,000 nm was measured using a Hitachi High-Tech Science Corporation "UH4150 UV-Visible Near-Infrared Spectrophotometer." The measurements were performed from the resin layer (β) side. There is no practical problem if the light transmittance at 500 nm is 75% or more and the light transmittance at 1,000 nm and 2,000 nm is 20% or less.
[0095] ≪Abrasion resistance≫ The scratch resistance of the prepared laminate was evaluated using a Gakushin-type friction fastness tester manufactured by Tester Sangyo Co., Ltd. A friction element (surface area 1 cm2) with a load of 1000 g was attached. 2 ) was attached with steel wool #0000, and the surface of the hard coat layer (1 cm x 15 cm) was reciprocated 10 times. After that, the number of scratches on the surface of the hard coat layer was counted and evaluated according to the following criteria. The fewer the number of scratches, the better, and if there are 10 or less scratches, it can be used without any problems in practical use. [Evaluation Criteria] 5: No scratches (0 pieces): Very good ·4: 1 to 5 scratches: Good 3: 6 to 10 scratches: Fairly good 2: 11 to 20 scratches: No problems in use 1: 21 or more scratches: Unusable
[0096] <Curling ability> The curling property of the produced laminate was evaluated by the following method: The laminate was cut into a size of 10 cm x 10 cm, and the average height of the lifted corners of the four corners was calculated. [Evaluation Criteria] 5: Less than 4mm: Very good 4: 4mm to less than 6mm: Good 3: 6mm to less than 8mm: Fairly good 2: 8mm to less than 10mm: No practical problems 1:10mm or more: Not practical
[0097] [Table 4-1]
[0098] [Table 4-2]
[0099] [Table 4-3]
[0100] As shown in Tables 4-1 and 4-2, it was confirmed that the laminate having the resin layer and the light-transmitting substrate formed by using the active energy ray curable composition of the present invention can have both scratch resistance and curling property, and further has excellent light transmittance in the visible light range and light blocking property in the near infrared range. This shows that the obtained laminate has excellent light transmittance in the visible light range, light blocking property in the near infrared range, transparency, scratch resistance, and curling property.
Claims
1. An active energy ray-curable composition comprising a compound (A) having three or more (meth)acryloyl groups, composite tungsten oxide particles (B), and a photopolymerization initiator (C), and which simultaneously satisfies the following (1) and (2): (1) The content of the composite tungsten oxide particles (B) in 100% by mass of the non-volatile components of the active energy ray-curable composition is 30 to 70% by mass. (2) In a test piece having a 1 μm-thick resin layer which is a cured product of an active energy ray-curable composition on a 50 μm-thick polyethylene terephthalate film, the haze is 1.0% or less, the total light transmittance is 65% or more, the light transmittance at a wavelength of 500 nm is 75% or more, and the light transmittance at wavelengths of 1,000 nm and 2,000 nm is 20% or less.
2. 2. The active energy ray-curable composition according to claim 1, wherein the composite tungsten oxide particles (B) are cesium-containing composite tungsten oxide particles.
3. 2. The active energy ray-curable composition according to claim 1, wherein the compound (A) contains a compound having six or more (meth)acryloyl groups.
4. The active energy ray curable composition according to claim 3, characterized in that the active energy ray curable composition contains 30 to 69 mass% of a compound (a1) having 6 or more (meth)acryloyl groups and having a cyclic structure, based on 100 mass% of non-volatile components.
5. A laminate comprising a light-transmitting substrate (α) and a resin layer (β) which is a cured product of the active energy ray-curable composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Photocurable resin composition, base material with cured coating film, and method for producing the same
JP2021055056A
Film with hard coat layer and window glass with hard coat layer
JP2022171369A
Active energy ray-curable composition and coated body
JP7210799B1
Radiation-sensitive resin composition, cured film, pattern formation method, solid-state image pickup element, and image display image
WO2017099019A1
Heat blocking film
WO2021045185A1